Normalized C-HH backscatter from Sentinel-1 (December, 2014-2017) for selected tundra regions. - Bartsch, Annett; Widhalm, Barbara; Pointner, Georg (PANGAEA, 2019)
Vegetation height has been derived from Sentinel-1 satellite data acquired in VV mode. Masking based on Sentinel-2 has been applied. Areas with NDVI < 0.4 are excluded for vegetation height retrieval in order to account for effects related to C-band scattering from rough and bare surfaces. Areas with VV < -15.4 dB (and NDVI > 0.4) are flagged as well as indicator for anomalous high values in vegetation related indices with at the same time low vegetation height. The remaining land area is assigned vegetation heights up to 160 cm. All heights > 160 cm are excluded and labelled as a separate class. Covered areas are: Yamal peninsula (Russia), Usa Basin (Russia), Lena Delta (Russia), Kytalyk (Russia), Mackenzie Delta (Canada), Umiuaq (Canada), Barrow (Alaska), Teshekpuk (Alaska), Toolik (Alaska) and Seward peninsula (Alaska). For more Information see the product documentation.
Vegetation height derived from Sentinel-1 and Sentinel-2 satellite data (2015-2018) for tundra regions
Keywords: Alaska, USA; AWI_PerDyn; C01_Barrow; C02_Toolik; C03_Teshekpuk; C04_Mackenzie_Delta; C05_Umiuaq; C06_Kytalyk; C07_Lena_Delta; C12_Seward-pen; Canada; DUE-GlobPermafrost; ESA Data User Element - GlobPermafrost; File content; File format; File name; File size; MON; Monitoring; NUNATARYUK; NUNATARYUK, Permafrost thaw and the changing Arctic coast, science for socioeconomic adaptation; Permafrost Research (Periglacial Dynamics) @ AWI; Siberia, Russia; T01_area-1; T01_area-2; T01_area-3; T01_area-4; T01_area-5; T01_area-6; T01_area-7; Uniform resource locator/link to file